1979
DOI: 10.5962/p.330830
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy of microvertebrate fossil assemblages

Abstract: Two principal modes of origin have been suggested for microvertebrate deposits -1) the scatological hypothesis, and 2) the fluvial hypothesis. These two hypotheses were tested by 1) examining remains found in modern carnivore feces and owl pellets, 2) experimentally determining the susceptibility of various skeletal elements of small mammals to stream sorting, and 3) analyzing microvertebrate fossil assemblages.The abraded rather than sharply broken condition of the fossil bone and the frequency of preservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
26

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 22 publications
(68 reference statements)
0
38
0
26
Order By: Relevance
“…The minimum number of individuals or MNI (Shotwell, 1955) for amphibians and mammals were calculated by counting the most frequent elements, taking into consideration the morphology of the elements, colour variation, and size of the elements. Relative representation (RR), the proportion of elements present relative to the expected number given MNI (RR=NISP observed/NISP expected elements) (Wolff, 1973;Korth, 1979) was calculated for these two groups in an attempt to compare these elements with Voorhies dispersal groups for hydraulic sorting.…”
Section: Techniques Employedmentioning
confidence: 99%
See 3 more Smart Citations
“…The minimum number of individuals or MNI (Shotwell, 1955) for amphibians and mammals were calculated by counting the most frequent elements, taking into consideration the morphology of the elements, colour variation, and size of the elements. Relative representation (RR), the proportion of elements present relative to the expected number given MNI (RR=NISP observed/NISP expected elements) (Wolff, 1973;Korth, 1979) was calculated for these two groups in an attempt to compare these elements with Voorhies dispersal groups for hydraulic sorting.…”
Section: Techniques Employedmentioning
confidence: 99%
“…In spite of many pioneering works on the taphonomy of megavertebrate fossils (Shotwell, 1955;Voorhies, 1969;Behrensmeyer, 1975Behrensmeyer, , 1988, very few studies have concentrated on the microvertebrate remains (Dodson, 1973;Mellett, 1974;Korth, 1979) in the past. Some workers (Dodson, 1973: Wolff, 1973Korth, 1979) have even cast doubt on their usefulness in the reconstruction of palaeocommunities because of the ease with which such elements are transported hydraulically or by predators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14). Korth (1979) suggested that small bone could be easily moved by very low currents of water competent to carry only the clay-sized fraction. Therefore, these bones would be sorted without being abraded.…”
Section: Taphonomymentioning
confidence: 99%